An optical buffer manipulation using a microring array - Punthawanunt, Suphanchai; Teeka, Chat; Jomtarak, Rangsan; Yupapin, Preecha P. (My University, 2011)
We present design and FDTD simulations of microring resonator array optical buffer. The proposed buffer consists of six microring array coupled via upper MZI arm and one microring coupled via lower MZI arm all coupled with 105 nm gap coupling. Results obtained have shown that the delay signals can be available for the use for optical memory and applications.
Keywords: Optical array; Optical buffer; Optical memory